THE DEVELOPMENT OF ATHLETES ENGLISH READING SKILLS AT THAILAND NATIONAL SPORTS UNIVERSITY - MEEWISATE, RAWIPA; SUJINTAVONG, PANITNAN; THANAIUDOMPAT, THANARIT (วารสารวิชาการวิทยาลัยสันตพล, 2026)
The objective of this research was to investigate the development of English reading comprehensive skills among undergraduate athletes at the Thailand National Sports University, Chon Buri Campus, using the jigsaw reading activity. The sample group for this study consisted of 10 first-year undergraduate athletes majoring in Sports Management within the Faculty of Liberal Arts. The instruments utilized in this research were seven lesson plans incorporating the Jigsaw Reading activity, each requiring three class periods, and seven subjective English reading comprehension tests designed to measure interpretive, critical, analytical, and summarizing comprehension levels is above 60 percent of the total score. Data analysis involved calculating percentages, means and standards deviation. The results indicated that the athletes' development in English reading comprehension met the established criteria, achieving an average percentage score of 86, which was categorized as 'satisfactory.' The learners consistently demonstrated a tendency toward continuous improvement in their English reading comprehension development.